2018
DOI: 10.9734/ejmp/2018/43846
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and Renal Biochemical Profile of Albino Rats Exposed to Chloroform and Methanol Leaf Extracts of Portulaca oleracea Linn.

Abstract: Portulaca oleracea Linn. is among the medicinal plants used globally in the treatment of diseases and management of health challenges. The dearth of information on the long term effect of Portulaca oleracea on hepatic and renal toxicity prompted this study. The study investigated the subchronic effect of the oral administration of chloroform leaf extracts of Portulaca oleracea (CLEPO) and methanol leaf extracts of Portulaca oleracea (MLEPO) on plasma activity of some enzymes (ALT, ALP & AST) and levels of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…A comparison of the acute oral toxicity testing of P. oleracea leaves in the previous studies [6,7] with P. oleracea stem in the present study, reveals that the chloroform extracts of both plant parts are not toxic since they were well tolerated by the animals at the maximum dose of 5000 mg/kg.…”
Section: Creatinine (µMol/l) Groupssupporting
confidence: 59%
See 3 more Smart Citations
“…A comparison of the acute oral toxicity testing of P. oleracea leaves in the previous studies [6,7] with P. oleracea stem in the present study, reveals that the chloroform extracts of both plant parts are not toxic since they were well tolerated by the animals at the maximum dose of 5000 mg/kg.…”
Section: Creatinine (µMol/l) Groupssupporting
confidence: 59%
“…The result of this study also shows that the chloroform stem extract of P. oleracea had no significant effect on the biochemical profile of exposed rats at the different doses and duration used in the study, unlike the leaf counterpart which altered the ALP and AST levels at different doses and duration; a significant decrease in AST level at the dose of 250mg/kg on Day 28 and a significant increase in ALP at the dose of 500mg/kg on Days 14 and 60 [7]. This finding suggests that the stem extract may lack the potential to reduce the plasma levels of the enzymes -AST, ALT and ALP by stabilizing the cell membrane of the source, in order to prevent the seepage of these enzymes, even in the absence of injury.…”
Section: Creatinine (µMol/l) Groupsmentioning
confidence: 59%
See 2 more Smart Citations
“…This assertion is supported by the work of Ezeabara et al [35] which demonstrated that the phytochemicals and nutrients found in various parts of Portulaca oleracea were in different concentrations. In our previous study carried out to investigate the hepatic and renal toxicity of chloroform (non-polar) and aqueous methanol(polar) leaf extracts of Portulaca oleracea on biochemical profile of albino rats, it was found that both extracts did not cause toxicity to the liver and kidney parameters assessed [36].…”
Section: Discussionmentioning
confidence: 98%